2018
DOI: 10.1190/tle37060412.1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ground truth images to validate micro-CT image-processing pipelines

Abstract: Digital rock technology and pore-scale physics have become increasingly relevant topics in a wide range of porous media with important applications in subsurface engineering. This technology relies heavily on images of pore space and pore-level fluid distribution determined by X-ray microcomputed tomography (micro-CT). Digital images of pore space (or pore-scale fluid distribution) are typically obtained as gray-level images that first need to be processed and segmented to obtain the binary images that uniquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 42 publications
3
41
1
Order By: Relevance
“…The resulting reconstructed image was first denoised using an edge preserving non-local means filter, then segmented using ZEISS Zen Intellesis machine learning based segmentation. Such a segmentation technique has been showed in quantitative benchmarks to be significantly more robust when dealing with such noisy and challenging images [34,35]. The resulting porosity observed within the image (41%) matched well with the inferred porosity of the 30µm x 30µm x 30µm region initially identified from the macroscopic 10µm voxel size image of the 10mm diameter core.…”
Section: Nano Scale Imagingsupporting
confidence: 54%
“…The resulting reconstructed image was first denoised using an edge preserving non-local means filter, then segmented using ZEISS Zen Intellesis machine learning based segmentation. Such a segmentation technique has been showed in quantitative benchmarks to be significantly more robust when dealing with such noisy and challenging images [34,35]. The resulting porosity observed within the image (41%) matched well with the inferred porosity of the 30µm x 30µm x 30µm region initially identified from the macroscopic 10µm voxel size image of the 10mm diameter core.…”
Section: Nano Scale Imagingsupporting
confidence: 54%
“…Chen and Zeng [10] demonstrated the capability of machine learning in rock facies classification from wireline log scalar attributes improving by feature augmentation. Compared to conventional image segmentation methods, machinelearning segmentation could come closer to the ground truth for determining the porosity from noisy MCT images (Berg et al [11]). Karimpouli and Tahmasebi [12] revealed that a CNN algorithm improves the accuracy of a segmentation comparing with a multiphase thresholding segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…There are many industrial applications of DR [3]: estimation of fluid transport properties such as absolute and relative permeabilities [4][5][6]; assessment of enhanced oil recovery (EOR) methods [7,8]; calculation of elastic moduli and electrical conductivity [9]; and modelling of nuclear magnetic resonance (NMR) response [10]. Figure 1 shows a typical DR workflow [11]. The first step is image acquisition by X-ray microcomputed tomography (microCT) [12].…”
Section: Introductionmentioning
confidence: 99%